Ketogenic effect of coconut oil in ALS patients - Carrera-Juliá, Sandra; Obrador, Elena; López-Blanch, Rafael; Oriol-Caballo, María; Moreno-Murciano, Paz; Estrela, José M. (Frontiers in Nutrition, 2024)
A recent pilot study in amyotrophic lateral sclerosis (ALS) patients analyzed the effect of a Mediterranean diet (MeDi) supplemented with nicotinamide riboside (NR, a NAD + promoter), pterostilbene (PTER, a natural antioxidant) and/or coconut oil on anthropometric variables in ALS patients. The results suggested that the MeDi supplemented with NR, PTER and coconut oil is the nutritional intervention showing the greatest benefits at anthropometric levels. Over the last 30 years, glucose intolerance has been reported in ALS patients. Thus, suggesting that an alternative source of energy may be preferential for motor neurons to survive. Ketone bodies (KBs), provided through a MeDi with a lower carbohydrate content but enriched with medium chain triglycerides, could be a therapeutic alternative to improve the neuromotor alterations associated with the disease. Nevertheless, the use of a coconut oil-supplemented diet, as potentially ketogenic, is a matter of controversy. In the present report we show that a MeDi supplemented with coconut oil increases the levels of circulating KBs in ALS patients.